EFFECTS OF CHLORELLA SUSPENSION AND SUPERVITA-M MULTIVITAMIN COMPLEX ON THE DEVELOPMENT OF INTERNAL ORGANS AND MEAT YIELD IN RABBITS - Nafisa Abdurakhmanova (Bright Mind Publishing, 2025)
The rabbit breeding industry plays a crucial role in the production of highly nutritious meat. The development of industrial rabbit farming requires the implementation of various biologically active substances and feeding systems aimed at improving the physiological condition, growth rate, and productivity of rabbits. In this regard, studying the effects of Chlorella suspension and the SuperVita-M multivitamin complex on the development of internal organs and post-slaughter meat yield in rabbits holds significant scientific and practical importance. This study aims to determine the mechanism of action of these supplements on the rabbit's body, assess the development of internal organs, and evaluate their impact on post-slaughter meat yield indicators.
Keywords: Rabbit, chlorella, suspension, supervita-M, multivitamin, internal organ, meat, yield.